Properties of Binary Blended Cement Mortars Containing Glass Powder and Steel Slag Powder - DAWOOD, Eethar Thanon; MHMOOD, Marwa Saadi (Engineering Transactions, 2021)
The large quantity of waste or by-product materials (such as waste glass and steel slag) released to landfills is considered to be a real problem. The use of these materials as cement replacements makes it possible to solve this problem and reduce the quantity of carbon dioxide emitted from the cement manufacturing process. This paper presents the effect of waste glass powder (GP) and steel slag powder (SSP) on the properties of blended cement mortar. The flow, compressive strength, direct tensile strength and dry density of cement mortar containing GP and SSP as cement replacements with and without superplasticizer (SP) are studied and compared with the control mix. The results show that the glass and steel slag powders, once they are simultaneously added as a ternary blended cement mortar, reduce the water binder ratio required to achieve flowability. Additionally, the compressive strength results of such blended mortar showed that the increased GP content exhibits better performance than that of slag powder for the same level of waste materials replacements.